China's High-Speed Rail Technology An International Perspective - Fang, Youtong; Zhang, Yuehong (Helen).; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents cutting-edge theories, techniques, and methodologies in the multidisciplinary field of high-speed railways, sharing the revealing insights of elite scholars from China, the UK and Japan. It demonstrates the achievements that have been made regarding high-speed rail technologies in China from all aspects, while also providing a macro-level comparative study of related technologies in different countries. The book offers a valuable resource for researchers, engineers, industrial practitioners, graduate students, and professionals in the fields of Vehicles, Traction Power Supplies, Materials, and Infrastructure.
Development and prospect of China Railway Technology -- China High-Speed Rail Technology -- China's High-Speed Railway Infrastructure -- China's High-Speed Rail Traction Power Supply, Communication Signals and Transport Organization -- Wheel-rail Dynamics of High Speed Train -- The Key Innovations of Materials for China's High-Speed Rail -- Comparison of China and other counturys' High-Speed Rail Technology.
Keywords: Transportation engineering; Traffic engineering; Electrical engineering; Mechanics, Applied; Materials; Transportation Technology and Traffic Engineering; Electrical and Electronic Engineering; Engineering Mechanics; Materials Engineering